KARAKTERISTIK BATUAN ASAL (BEDROCK) PEMBENTUKAN NIKEL LATERIT PADA DAERAH X DAN SEKITARNYA KABUPATEN MOROWALI UTARA SULAWESI TENGAH - Andarias Biney; Amara Nugraheni; Herning Dyah Kusuma Wijayanti (KURVATEK, 2022)
Abstract Administratively, the research area is included in North Morowali Regency, Central Sulawesi Province, Central Java Province, which is in the 49 S zone with UTM (Universal Transverse Mercator) coordinates 9152800 – 9152800 400800 - 406800 mE with an area of ​​± 54 km2 (9 km x 6 km). ). One of the factors that influence the formation of laterite nickel deposits is the source rock. The purpose of this research is to focus on the characteristics of the original rock, namely ultramafic rock based on the intensity of serpentinization, its constituent minerals, and its relation to the laterization potential of nickel deposits in area X and its surroundings, North Morowali Regency, Central Sulawesi. The research method used is literature study, field activities (surface mapping), data processing (laboratory analysis and studio analysis), and report generation. Based on megascopic data, the research area consists of three units, namely alluvial units, peridotite rock units and limestone units. Based on petrographic analysis, the characteristics of the original rock in 10 rock samples were dominated by dunite and followed by serpentinized dunite, harzburgite, lerzolite, wehrlite, and serpentinite. The main mineral compositions in the rock are olivine, clinopyroxene, orthopyroxene, and group serpentine (antigorite, lizardite and talc). Laterite distribution in the research area is dominated by rocky laterite and laterite, with the prospect area being in the eastern part of the study area. The distribution of serpentinization zones based on the intensity level of serpentine minerals in the rock, found in the western hills is dominated by very low-medium serpentinization, while the eastern hills are dominated by low-high serpentinization. Key words : Origin Rock, Laterite, North Morowali, Petrography, Serpentinization